Virtual Q&A Transcript of the 2021 "Contemporary Appalachian Photography Panel Discussion". - SLIGH, CLARISSA; SEE, LYDIA; KING, MEGAN; CALDWELL, SHAUNA (Appalachian Journal)
Transcription of virtual Q&.A during Contemporary Appalachian Photography: Panel Discussion" with artists Clarissa Sligh, lydia see, Megan King, andMadison Hye Long facilitated by shauna caldwell and hostedby the Turchin Center for the Visual Arts as part of the Appalachian Mountain Photography Competition on March 24, 2021. (Madison Hye Long unfortunately could not be part of the (2&A portion of the event).